Adoção e uso da tecnologia da informação por produtores e cooperativas da cadeia produtiva do leite - Figueira, Aleandra da Silva (2003)
Information technology (IT) is being considered as the restructuring agent of environment and inner and outer functions oforganizations, with the objective of connecting peopíe, processes and companies. IT is also consolidating in the agribusiness organizations ofmilk in a slower manner. This work had the objective ofstudying the adoption and use ofIT by producers and cooperatives of the milk production chain in Southern Minas Gerais, emphasizing the utilized structure, reasons of adoption, difficulties faced, proportioned impacts and competitive dimension of IT. The methodology utilized was based on qualitative research, through exploratory and descriptive study, also fitting in the case study method. Two cooperatives and two associated producers were selected to compose the units ofanalysis. Regarding these organizations, the following can be distinguished: producers give priority to generic equipment and software, while cooperatives invest in integrated management hardware as well as in software. Regarding the reasons, the two segments searched for internai control and management ofthe organizations. Due to low education levei ofworkers, resistance was the main difficulty faced by producers and cooperatives, however it was eased by training. lt was observed that IT proportioned coordination in activities, agility in information, more attention and responsibility by part ofworkers and reduction oferrors in the internai operations. Regarding competitiveness, IT has helped the segments in the intransigent competitive market, by controlling internai activities and actions. The study allowed verifying the lack ofpreoccupation ofproducers and cooperatives with the externai environment ofthe productive chain, or in other words, the priority is the intra-organizational process. The intervention of the govemment could contribute by encouraging the use ofIT in the relationship of agents ofthe milk production chain.